Immigrant Student Achievement and Education Policy Cross-Cultural Approaches (Policy Implications of Research in Education,, 2018)
This book examines immigrant student achievement and education policy across a range of Western nations. It is divided into 3 sections: Part 1 introduces the topic of immigrant student achievement and the performance disadvantage that is consistently reported across a range of international jurisdictions. Part 2 then presents national profiles from scholars in ten countries (England, Germany, Italy, Sweden, Finland, Netherlands, Republic of Ireland, Canada, Australia, and New Zealand). These educational jurisdictions were selected because they represent a range of Western nations engaged in large-scale reform efforts geared towards enhancing their immigrant students' achievement. Each of the national profiles provides a brief overview of the evolution of the cultural composition of their respective school-aged student population; explains the trajectory of achievement results in non-immigrant and immigrant student groups in relation to both national and international large-scale assessment measures; and discusses the effectiveness of policy responses that have been adopted to close the achievement gap between non-immigrant and immigrant student populations. It also examines the relationships between education policies and immigrant student achievement and discusses how education policies have evolved across various cultural contexts. In conclusion, Part 3 analyzes cross-cultural approaches designed to address the performance disadvantage of immigrant students and proposes future areas of inquiry stemming from the national profiles. The book offers insights into a diverse cross-section of nations and policy approaches to addressing the performance disadvantage. .